A route towards the fabrication of 2D heterostructures using atomic layer etching combined with selective conversion. (16th May 2019) - Heyne, Markus H; Marinov, Daniil; Braithwaite, Nicholas; Goodyear, Andy; de Marneffe, Jean-François; Cooke, Mike; Radu, Iuliana; Neyts, Erik C; De Gendt, Stefan
Abstract: Heterostructures of low-dimensional semiconducting materials, such as transition metal dichalcogenides (MX2 ), are promising building blocks for future electronic and optoelectronic devices. The patterning of one MX2 material on top of another one is challenging due to their structural similarity. This prevents an intrinsic etch stop when conventional anisotropic dry etching processes are used. An alternative approach consist in a two-step process, where a sacrificial silicon layer is pre-patterned with a low damage plasma process, stopping on the underlying MoS2 film. The pre-patterned layer is used as sacrificial template for the formation of the top WS2 film. This study describes the optimization of a cyclic Ar/Cl2 atomic layer etch process applied to etch silicon on top of MoS2, with minimal damage, followed by a selective conversion of the patterned Si into WS2 . The impact of the Si atomic layer etch towards the MoS2 is evaluated: in the ion energy range used for this study, MoS2 removal occurs in the over-etch step over 1–2 layers, leading to the appearance of MoOx but without significant lattice distortions to the remaining layers. The combination of Si atomic layer etch, on top of MoS2, and subsequent Si-to-WS2 selective conversion, allows to create a WS2 /MoS2 heterostructure, with clear Raman signals and horizontal lattice alignment. These results demonstrate a scalable, transfer free method to achieve horizontally individually patterned heterostacks and open the route towards wafer-level processing of 2D materials.